Artificial cell membrane binding thrombin constructs drive in situ fibrin hydrogel formation - Robert C. Deller (Nature Portfolio, 2019)
The incorporation of cells into tissue engineering scaffolds can be a major challenge. Here, the authors report on anchoring thrombin to cell membranes for the in situ formation of fibrin scaffolds around the modified cells, demonstrate scaffold formation in vitro and show cell survival in vivo.